005 Rectal bleeding presenting to the paediatric emergency department. Issue 12 (21st November 2019) - Evans, Jordan; Metezai, Huria; Roberts, Zoe
Abstract : Background: Bleeding per rectum in infants and children is often an alarming symptom for caregivers. The differential diagnosis is wide, from the benign to life-threatening. The current literature is limited on the description of this undifferentiated population in the UK. We aimed to describe the frequency of this presentation, the most common diagnoses and current management in the Paediatric Emergency Department (PED). Method and results: Retrospective case note review of all patients presenting to a tertiary PED within a two year period from April 2017 to March 2019, with blood in stool/per rectum. Cases were identified by reviewing all presenting complaints including the words 'blood' or 'bleed'. Data was collected using a standardised data collection form for the following variables; age, sex, diagnosis in PED, urgent intervention required, diagnosis on follow-up, diagnostic concordance between PED and follow-up diagnosis, investigation (stool, blood, imaging), admission, outpatient referral and reattendance during thestudy period. Conclusions: A total of 90 cases were identified, 10 were excluded as they did not meet inclusion criteria (n=80). This made up 0.14% of all presentations to the PED within the two year period. Mean age was 5 years (3 months - 15 years) with 51% female and 49% male. Collectively constipation and gastroenteritis accounted for 76% of diagnoses. 24% of patients were admitted the same day and 38% referred for outpatient follow up. There was agreement between PED diagnosis and outpatient diagnosis in 87% of cases. 5% of cases required urgent intervention. Bleeding per rectum is an infrequent presentation to the PED. The most common diagnoses are benign and many cases may be managed without need of admission or outpatient follow up. A high index of suspicion remains necessary to identify infrequent but serious pathology. There is currently limited evidence to guide practice and therefore further work is required.